Business analytics - Bag, Dinabandhu (London Routledge, 2017)
This book provides a first-hand account of business analytics and its implementation, an account of the brief theoretical framework underpinning each component of business analytics, and gives a complete insightful understanding of developing and implementing analytical solution.
Introduction -- Business roles -- Functional analytics -- Human resource analytics -- Supply chain analytics -- Customer analytics -- Business process analytics -- Financial analytics -- Implementing business analytics -- Use cases and business application.
Keywords: Management -- Statistical methods; Decision making -- Statistical methods